Management of learners with conduct disorders in Nkayi Rural District Primary Schools in Zimbabwe. - Siziba, Khumbulani; Kaputa, Thomas Musankuleni (Journal of Research in Social Science and Humanities, 2023)
Zimbabwe has adopted an inclusive education system in order to address barriers to learning for children with conduct disorders. The management of learners with conduct disorders is hampered by the lack of teachers’ skills and knowledge in guidance and counselling of learners with conduct disorders. In this paper, the researcher identifies the challenges in the management of learners with conduct disorders in Nkayi District primary schools and explores suggestions on the best and convenient ways of managing these learners. A qualitative research approach and a phenomenological research design were employed in which ten teachers in rural primary schools were interviewed to solicit their views, experiences and observations on the management of learners with conduct disorders in primary schools. The study concluded that the management of learners with conduct disorders in rural primary schools may not be successful without considerate guidance and counselling modalities in schools.